Raw bioelectrical impedance parameters and vector analysis in the screening of low muscle mass and low muscle mass associated with obesity in adult healthy subjects - Bennouar, Salam; Bachir Cherif, Abdelghani; Raaf, Nabil; Hani, Hadda Meroua; Kessira, Amel; Abdi, Samia (Internal and emergency medicine, 2025)
The aim was to estimate the prevalence of low muscle mass (LMM) and low muscle mass associated with obesity (LMM-O) in healthy adult, and to verify the performance of raw bioelectrical impedance parameters (BIA) and vector analysis (BIVA) in the screening of this tow conditions. This is a cross-sectional study including 1025 healthy adults. Body composition was assessed by the BIA technique. The appendicular skeletal muscle mass index (ASMMI) and body fat percentage (BF%) were used for the screening of LMM and LMM-O. The raw BIA parameters were: resistance ( R ), reactance ( X c ), phase angle (PhA), and impedance ( Z ). The vectors, R and X c , were adjusted for height and projected on the RX c graph. Associations were checked by the correlation test, binary logistic regression, adjusted for age and body water, and ROC curve. LMM was found in 30.8% of the subjects, and 20.9 and 21.4% of the men and women were with LMM-O. PhA and R / H were the most powerful discriminators of LMM with a sensitivity of 62–100% and a specificity of 71–90%. Cutoff values of PhA ranged between 4.95° and 5.75° for women and men. The RX c graph was able to identify LMM subjects, with clustering on the right side: area of low cellularity, high R / H and low-phase angle. Traditional anthropometric indices were the least effective in identifying LMM-O. The BIVA approach, PhA, R and R / H are effective in the screening of LMM and LMM-O, irrespective of age, gender, intra- and extracellular hydration status